Perceived Stress and Resilience among Nurses Working in a Selected Hospital at Mangalore - Kannappan, Sujatha R.; Veigas, Jacintha (Journal of Health and Allied Sciences NU, 2021)
Objective A minimum amount of stress is essential for a successful life. When it goes beyond the limit, it affects overall well-being. There is a need to modify the environment, feelings, and physical factors of an individual to promote resilience. This study aimed to assess and find the relationship between perceived stress and resilience among nurses working in a selected hospital.Materials and Methods The investigators used the descriptive correlation design and, through the nonprobability sampling method, selected 65 nurses. Data was collected using the demographic variables, perceived stress scale, and the Connor–Davidson resilience scale.Results and Discussion The investigators found a moderate level of stress (61.5%) with intermediate resilience (73.8%) among the nurses and noted a weak correlation between perceived stress and resilience (calculated value is 0.226 and the p-value is 0.071). There was an association found between the frequency of night duty, education level, and perceived stress.Conclusion Our study showed that most of the nurses had a moderate level of stress with intermediate resilience. The unmarried nurses were more resilient, with a moderate level of stress than the married.
Keywords: psychological; adaptation; nurse-midwives; resilience; stress